2-(2-Methoxyphenyl)-1,3-dimethyl-1H-benzoimidazol-3-ium iodide as a new air-stable n-type dopant for vacuum-processed organic semiconductor thin films. - Wei, P; Menke, T; Naab, B; Leo, K; Riede, M; Bao, Z (American Chemical Society, 2012)
2-(2-Methoxyphenyl)-1,3-dimethyl-1H-benzoimidazol-3-ium iodide (o-MeO-DMBI-I) was synthesized and employed as a strong n-type dopant for fullerene C(60), a well-known n-channel semiconductor. The coevaporated thin films showed a maximum conductivity of 5.5 S/cm at a doping concentration of 8.0 wt% (14 mol%), which is the highest value reported to date for molecular n-type conductors. o-MeO-DMBI-I can be stored and handled in air for extended periods without degradation and is thus promising for various organic electronic devices.